Reliability assessments of single and three-phase representation of LV distribution network - Muhamad, Ikhwan Hafiz; Daniyal, Hamdan; Sulaiman, Mohd Herwan; Mohd Hafizi, Ahmad (2020)
Most of the existing studies prefer modelling of distribution networks as symmetrical three-phase networks, using the corresponding single-line network representations, as that substantially simplifies the analysis. Generally, this assumes that the protection components (e.g. circuit breakers or fuses for “feeder cut-off”, i.e. disconnection of faulted feeders) operate in a three-pole mode of operation. This means that for asymmetrical single-phase and double-phase faults, which are typically 5-6 times more frequent than the three-phase faults, the protection component will disconnect all three phases, not just the faulted one(s). Generally, this reflects the correct application and setting of the three-pole protection systems in MV networks, but it is not likely for the LV networks, where most of the customers are connected to a single-phase 230 V supply and where fuses, as the most common protection components, are operated in a single-pole mode. Conversely, using a single-line representation of LV networks means that there will be no distinction between the different fault types and that the assessed number of interrupted customers will be significantly overestimated. Accordingly, if this aspect of the LV network design is not accurately modelled, the assessment of reliability performance of LV networks will not be correct.